Cortisol in Oral and Maxillofacial Surgery: A Double-Edged Sword - Muslat A Bin Rubaia’an; Muath Khaled Alotaibi; Naif Mutlaq Alotaibi; Nasser Raqe Alqhtani (International Journal of Dentistry)
Cortisol is a hormone that is naturally produced by the zona fasciculata of the cortex in the adrenal gland. One of its main functions is to decrease inflammation, particularly in areas where an inflammatory response is not necessary. In the field of oral and maxillofacial surgery, cortisol is used to improve the outcomes of surgical procedures and to make the postoperative period more comfortable for the patient. However, cortisol is considered a double-edged sword because its use is associated with both benefits and adverse effects. It is imperative to use cortisol following an accurate diagnosis, in addition to clarity regarding the desired surgical procedure for treating the acute or chronic condition affecting the patient. When used with caution, cortisol can serve as a valuable agent for reducing the postoperative inflammatory response in patients undergoing moderate as well as moderately severe surgical procedures.